Transformational Curriculum Model through Interpretation Epistemology; Islamic Boarding School Curriculum Management Perspective - Junaedi, Junaedi; Syafi'i, Imam; Hasyim, Fuad; Jawid Marwat, Mohammad (Munaddhomah: Jurnal Manajemen Pendidikan Islam, 2025)
This study examines the epistemological foundations of Qur'anic interpretation (tafsir) within the curriculum of traditional Islamic boarding schools (Pesantren) in the Nusantara, with a focus on integrating classical and contemporary interpretative methodologies into curriculum management. Employing a qualitative approach through library research, historical tracing, and content analysis of canonical tafsir texts (such as Tafsir Jalalayn, Ibn Kathir, and Baidhawi) alongside institutional documents, the research traces the evolution of tafsir education across generations. The study covers Pesantren of the salaf (clasic) (Langitan, Lirboyo, Blokagung), khalaf (modern) (Gontor, Al-Azhar Medan, Al-Amanah Sidoarjo), and hybrid (Tebuireng, Al-Munawwir Krapyak, Darunnajah Jakarta) typologies. Findings indicate that while the classical naqli-based approach remains dominant, there has been a gradual integration of ʿaqli-contextual methods, characterized by thematic and rational interpretations, aimed at addressing contemporary issues such as pluralism, public ethics, and democracy. This study proposes a layered curriculum model grounded in epistemological progression, organizing tafsir learning from traditional texts at the foundational level to reformist and thematic interpretations at the advanced level. Such a model bridges the preservation of Islamic scholarly heritage with contemporary relevance (ṣāliḥ li kulli zamān wa makān), reinforcing the role of Pesantren as centers of Islamic learning that produce graduates with strong textual competence and ethical sensitivity toward social realities.